Identifying Critical Success Factors in Implementing Green Building, Case Study: Medium-sized Construction Companies in East Java, Indonesia - Arwani, M Hamizan Najib; Negara, Kartika Puspa; Setyowulan, Desy (ASTONJADRO, 2025)
The construction industry is a significant consumer of natural resources and a contributor to environmental issues and ecological instability. This has led to the emergence of sustainable programmes (green construction) which aim to minimise the impact of development projects. The objective of this study is to identify the critical success factor in implementing green construction and to the extent of familiarity among middle-sized companies in the province of East Java with the implementation of green construction projects and to ascertain the factors that affect the success of such projects. The case study subjects are four medium-sized construction companies in East Java that have experience in implementing green building projects. The data obtained will be analysed on mean using IBM SPSS software on each variable. The results will identify the top five critical success factors based on questionnaires distributed to respondents. The findings of critical success factors are as follows: Integrated planning and/or design, Adequate project funding sources (smooth payments), Classification/capabilities of implementing contractors, Effective communication among stakeholders, Competence and experience of the project manager, and last critical success factor is Applicable policies/regulations regarding green construction. These findings are expected that this research will contribute to a deeper understanding of the critical factors that influence success in implementing green construction projects.